Self perceived work related stress and the relation with salivary IgA and lysozyme among emergency department nurses. Issue 12 (1st December 2002) - Yang, Y; Koh, D; Ng, V; Lee, C Y; Chan, G; Dong, F; Goh, S H; Anantharaman, V; Chia, S E
Abstract : Aims: To assess and compare the self perceived work related stress among emergency department (ED) and general ward (GW) nurses, and to investigate its relation with salivary IgA and lysozyme. Methods: One hundred and thirty two of 208 (63.5%) registered female ED and GW nurses participated in the study. A modified mental health professional stress scale (PSS) was used to measure self perceived stress. ELISA methods were used to determine the salivary IgA and lysozyme levels. Results: On PSS, ED nurses had higher scores (mean 1.51) than GW nurses (1.30). The scores of PSS subscales such as organisational structure and processes (OS), lack of resources (RES), and conflict with other professionals (COF) were higher in ED than in GW nurses. ED nurses had lower secretion rates of IgA (geometric mean (GM) 49.1 μg/min) and lysozyme (GM 20.0 μg/min) than GW nurses (68.2 μg/min, 30.5 μg/min). Significant correlations were observed between PSS and log IgA and lysozyme secretion rates. OS, RES, and COF were correlated with log IgA and lysozyme levels. Conclusion: ED nurses, who reported a higher level of professional stress, showed significantly lower secretion rates of salivary IgA and lysozyme compared to GW nurses. Salivary IgA and lysozyme were inversely correlated with self perceived work related stress. As these salivary biomarkers are reflective of the mucosal immunity, results support the inverse relation between stress and mucosal immunity.